DESIGNING AN OMNICHANNEL MARKETING BUSINESS MODEL TO IMPROVE CUSTOMER EXPERIENCE - Afandi, Yosi; Maskur, Maskur; Fiernaningsih, Nilawati; Herijanto, Pudji (Transpublika Publisher, 2024)
System integration allows companies to bring together customer data from multiple channels, from websites to mobile apps and physical stores. Companies can have a more complete view of customer preferences and behavior, which in turn allows them to serve more relevant and personalized content to their customers. In an era where customers are inundated with information, content personalization is key to attracting customers' attention and maintaining their engagement. Furthermore, this business model emphasizes deep customer engagement across multiple channels. In an omnichannel environment, it is important for companies to stay connected with their customers no matter where they are. This can be achieved through responsive customer service, ongoing loyalty programs, and engaging content on social media and other online platforms. The results of this study discuss the analysis of application quality using five characteristics, namely Functional Suitability, Usability, Performance Efficiency, Portability and Compatibility. The results of the functional suitability characteristics of the omnichannel platform are said to be good. Usability gets 76.67% which means the omnichannel platform is called feasible. Performance efficiency of the website is good because the load process is less than 10 seconds. From these results it is concluded that the Omnichannel platform meets the predicate of satisfied. Compatibility of the Omnichannel platform did not find any location and performance problems on Edge, Chrome and Android browsers. The assessment results are expected to be recommendations and suggestions for developing an omnichannel platform to help the process of sending digital reminders that are better and more efficient.